Avaliações psicológicas e decisões judiciais em processos de alienação parental - Fermann, Ilana Luiz (2016)
The Parental Alienation (PA) is a phenomenon which commonly occurs in child custody situations and affects children and adolescents. Although it is considered a current theme and there is a law in Brazil that configure the AP as a negative psychological interference, studies that portray these situations are still insufficient. The objective of this research was to the describe cases of AP, through the analysis of judicial processes and verify the criteria used by the professionals of psychology in the evaluation of these cases. The research is organized in two empirical studies. The empirical study titled 1 “Characterization of Judicial Processes of Parental Alienation in Brazil” characterized judicial processes PA, including the profile of the children, their parents and information about the processes. They analyzed 14 judicial processes and the results indicated that most of these did not report the initial complaint and PA were related to visitation and custody of property after divorce. Mothers were identified as alienating and alienated father as in most cases. Children were predominantly only daughters, they were under the care of mothers and attended elementary school. The empirical study titled 2 “Psychological expertise in Parental Alienations Cases” verify the criteria, indicators, methods and procedures used by psychologists in cases of PA and assessed the adequacy of psychological reports contained in legal proceedings in accordance with the guidelines of the Federal Council of Psychology (FCP). Eight reports have been identified in processes analyzed and it was found that none of the documents presented structure required by the FCP. Interviews were the most used procedures and few professionals included testings. Problems such as lack of integration of the results with the findings and suggestions of legal measures were observed in the expert reports. Finally, in only half of the eight cases containing report was verified correlation between psychological expert conclusion and the court judgment on the presence or absence of PA.